Faktor-Faktor Yang Berhubungan Dengan Perilaku Seksual Remaja Di Kabupaten Bulukumba - Arfiani Arfiani; Husnul Khatimah; Kurniati Akhfar (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
Based on 2013 BKKBN data, the number of sexual behaviors among adolescents aged 14-19 years reached 41.8 percent. This research aims to determine the factors related to sexual behavior in adolescents at SMA Negeri "X" Bulukumba with the variables studied including independent variables, namely age, gender, knowledge, attitudes, role of parents, role of peers, mass media and social environment, while the dependent variable is sexual behavior. This research is an analytical study, the design used in this research is cross sectional, the sample size is 158 using the scientific proportional formula, questionnaire measuring instruments. The results of this research are a description of sexual behavior in students of SMA Negeri "X" Bulukumba. It is known that out of 158 respondents it turns out Data obtained on sexual behavior at serious risk was less, namely 35.4%, compared to mild risk, namely 64.6% and in this study the variables that were not related were attitude with a P value of 0.286, the role of parents with a P value of 0.162 and social environment. with a P value of 0.061